Studi Komparatif Regulasi Diri dalam Belajar pada Mahasiswa yang Bekerja dan Mahasiswa yang tidak Bekerja - Prabawaningrum, Anita Budi; Sarajar, Dewita Karema (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2024)
Undergraduate students should ideally focus on their academic achievements; however, it is currently expected to find undergraduates who work while attending college. Regardless of whether students work while attending college, students must have self-regulation in learning to follow the learning process effectively. This is because learning in the realm of higher education relies on students' independence. This research aims to determine the differences in self-regulation in learning between working and non-working undergraduate students. The research method used is quantitative comparative with the Independent sample t-test analysis method. In this study, 316 students, comprising 158 working students and 158 non-working students, participated in this research using convenience sampling. The scale used in this study is the Self-Regulation in Learning Scale (α = 0.901). This research found no significant difference in self-regulation in learning between working and non-working students, with a significance level of 0.275 (p > 0.05). This means that the hypothesis in this research is rejected. Working students have higher categories in motivation, behavior, and context aspects. Meanwhile, non-working students tend to score higher in the cognition aspect. The findings of this research also provide an overview that external conditions of students do not significantly affect self-regulation in learning.